Strategi transformasi digital dalam meningkatkan daya saing dan kinerja perusahaan di era artificial intelligence (ai) - Nisa, Siti Khoirun (Maliki Interdisciplinary Journal, 2025)
The development of digital technology in the Industrial Revolution 4.0 era has brought about major changes in the way companies work and compete. One of the most influential technologies is Artificial Intelligence (AI), which helps companies become more efficient, faster, and innovative. This article discusses how digital transformation strategies can improve company competitiveness and performance in the AI ​​era. This research uses a literature review method by reviewing various relevant journals. The results of the study indicate that the implementation of technologies such as AI, big data, cloud computing, and the Internet of Things (IoT) can improve work efficiency, service quality, and a company's innovation capabilities. However, the success of digital transformation depends not only on technology but also on the readiness of human resources, leadership that is open to change, and an adaptive organizational culture. Challenges such as data security, the ethics of AI use, and low digital literacy still need to be addressed. Therefore, digital transformation strategies must be implemented comprehensively, ethically, and sustainably so that companies can continue to grow and compete in the era of artificial intelligence.